Efficacy of single-step transepithelial photorefractive keratectomy in myopia, hyperopia and astigmatism-a systematic review - Sharmeen Akram; Wardah Moazzum; Khadijah Abid (BMC Ophthalmology, 2025)
Abstract Background This systematic review assesses the efficacy of single-step transepithelial photorefractive keratectomy (tPRK) in terms of postoperative pain, epithelial healing, postoperative haze and visual acuity. It also compares single tPRK to two-step tPRK where data is available. Methods This systematic review adhered to the PRISMA reporting guidelines (Preferred Reporting Items for Systematic Reviews and Meta-analyses). An electronic literature search was conducted on PUBMED, Scopus, and Google Scholar. The quality of the studies included in this systematic review was evaluated using the Newcastle Ottawa Scale (NOS). The protocol of this systematic review was registered on PROSPERO with ID CRD42024494717. Results A total of 11 studies published between 2013 and 2023 were included in this systematic review. Studies revealed a significant improvement in visual acuity with both single-step tPRK and two-step tPRK. Two studies showed that single-step tPRK not only offers a better UDVA but also a significant improvement in the manifest sphere, cylinder, and spherical equivalent at various follow-up periods compared to two-step tPRK. One study demonstrated the broad effectiveness of single-step tPRK for myopia correction across low-, moderate-, and high-severity groups. Rapid epithelial healing was a consistent finding. Complete epithelial healing within 72 h was noted in 100% of eyes treated with single-step tPRK in one of the studies. The incidence of corneal haze following tPRK was generally low across the studies. Post-tPRK pain scores were initially lower in the single-step tPRK group. One study reported that the maximum pain level within the first four days after surgery was significantly lower in the single-step tPRK group than in the two-step tPRK group. Conclusion Both two-step and single-step tPRK are safe refractive procedures. Single-step tPRK, because of less haze formation, lower pain scores, faster healing, and greater effectiveness in improving visual acuity, is superior to the two-step technique. Trial registration The protocol of this systematic review was registered on PROSPERO with ID CRD42024494717.